2009
DOI: 10.1103/physrevb.79.134101
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in beryllium: Solubility, transport, and trapping

Abstract: The paper presents the results of ab initio simulation of hydrogen properties in beryllium. Both interstitial hydrogen positions in the lattice and various hydrogen positions in a vacancy have been studied. The most energetically favorable interstitial hydrogen configuration among the four considered high-symmetry configurations is the basal tetrahedral one, in agreement with the earlier predictions. The most probable diffusion pathway for hydrogen atoms in the bulk involves the exchange of octahedral and basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
41
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 52 publications
11
41
1
1
Order By: Relevance
“…To reliably simulate this process, one should know the atomic scale mechanisms of helium diffusion and interaction of helium with traps. The properties of vacancy and interstitial type defects as well as preliminary results on helium behavior in beryllium were previously studied using ab initio methods [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…To reliably simulate this process, one should know the atomic scale mechanisms of helium diffusion and interaction of helium with traps. The properties of vacancy and interstitial type defects as well as preliminary results on helium behavior in beryllium were previously studied using ab initio methods [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous DFT studies have demonstrated that donor atoms in Ge associate with V forming complexes. [15][16][17][18][19] Equivalent methods have also been used in conjunction with experimental and Monte Carlo techniques to study phosphorus-vacancy ͑PV͒ pairs in Si and silicon germanium alloys ͑SiGe͒, 20,21 and AsV pairs in Si. 22 In a recent DFT study, the stability of complexes formed between C atoms and donor-vacancy ͑AV͒ pairs was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…under high-pressure compaction-fusion of amorphous BeH 2 catalyzed by lithium. 12 While suffering from a toxicity issue, bulk BeH 2 has the highest hydrogen weight percentage of 18.2 wt% and moderate hydrogen desorption temperature of about 250 C. 13,14 Recently, its non-bulk forms, BeH 2 nanoparticles, and line-style [BeH 2 ] n nanoclusters, have been successfully synthesized in experiment for hydrogen storage due to the large surface to volume ratios at the nanoscale level, [15][16][17][18][19] which raised further interest in its low dimensions such as two-dimensional (2D) form.…”
Section: Introductionmentioning
confidence: 99%